PENGARUH PENILAIAN FORMATIF DENGAN FEEDBACK TERHADAP PROSES DAN HASIL BELAJAR PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Farina, Jeli (2014)
Penelitianinibertujuanuntukmengungkapkanpengaruhpenilaianformatifdenganfeedbackterhadap proses danhasilbelajarpadamateripokokkelarutandanhasil kali kelarutan. Penelitianinimerupakanpenelitian Quasi eksperimendengannonequivalent pretest-postestcontrol group design. Jumlahsampelpadakelaseksperimensebanyak 32 siswadankelaskontrolsebanyak 32 siswa.Bentuktesformatif yang digunakandalampenelitianiniadalahkuisdanhomework.Siswapadakelaseksperimenmendapatkuissetiapakhirpembelajarankemudiansiswamendapatfeedbackdalambentuktulisandan verbal.Sedangkansiswapadakelaskontrolhanyadiberikuissetiapakhirpembelajarantanpafeedbackdari guru.Berdasarkanhasilanalisis data diperoleh rata-rata n-gainsebesar 0,53untukkelaseksperimendan 0,29 untukkelaskontrol. Hasilsignifikansidiperolehsebesar 0.002 lebihkecildari 0.05 yang bermaknabahwaterdapatperbedaansignifikan rata-rata gain yang dinormalisasikelaseksperimendengankelaskontrol. Kemudiandarihasilperhitungandiperoleheffect sizesebesar 0.85 yang termasukkedalamkategoritinggi.Hasilpenelitianmenunjukkanbahwapenerapanpenilaianformatifdenganfeedbackdalampembelajaranberpengaruhpositifterhadap proses belajarsiswa.Siswamenjadilebihantusias, termotivasi, danlebihaktifselamapembelajaran.Berdasarkanpenelitianinidapatdisimpulkanbahwapenerapanpenilaianformatifberpengaruhpositifterhadap proses belajarsiswadanmeningkatkanhasilbelajarsiswa. The aim of this study was to find impact of formative assessment with feedback to learning process and students learning outcomes on solubility and constant solubility product. The method used on this study was quasi experiment research with nonequivalent pretest-postestcontrol group design. Samples on this study were consisted 32 students of experiment class and 32 students of control class. Formative test's used quiz and homework, students on experiment class gave quiz each last learning in a day then students got written feedback and verbal feedback. Students on control class was only get quiz without feedback by teacher. The N-gain of experiment class is 0,53 and 0,29 in control class. The significantly result based independent t test is 0.002 more less than 0,05 that means average of n-gain significantly different between experiment class and control class and the effect size is 0,85. The result showed that application of formative assessment with feedback on learning has positive impact toward students learning process. Students come more enthusiastic, motivated, and more active on learning. Thus in this study can be conclude that formative assessment with feedback have positive impact toward learning and increases students outcomes learning. Keywords: Formative assessment, feedback, learning process, and students outcome learning.